The farm on the roof : what Brooklyn Grange taught us about entrepreneurship, community, and growing a sustainable business - Plakias, Anastasia Cole (Avery, an imprint of Penguin Random House, 2016)
In their effort to build the world's first and largest commercial green rooftop farm, the founders of Brooklyn Grange learned a lot about building and sustaining a business while never losing sight of their mission to serve their community by providing delicious organic food and changing the way people think about what they eat.